A Novel Line Current Control Strategy to Control the Real Power Flow at PCC using H-bridge Inverter - Qusay Salem; Jian Xie (Institute of Advanced Engineering and Science, 2018)
This paper presents the power flow control between the main grid and the microgrid in low-voltage distribution network using H-bridge inverter. Controlling the real power flow in the line using the H-bridge inverter is investigated by implementing the line current control strategy. The feasibility of the proposed H-bridge inverter and its control strategy is validated by varying the line current reference. Hence, the H-bridge inverter will operate in its inductive or capacitive operation mode depending on the reference current value and the output of the PI controller in the control unit. The control strategy of the microgrid distributed generators has also been investigated in which P/V droop characteristics is applied to the power control of each DG in the microgrid. The effectiveness of the proposed approaches is validated through simulations.